Characteristics of training condition of adolescence rowers - E. Kharlamov; N. Popova; I. Zhuchkova; A. Menkova (National Electronic Information Consortium (NEICON), 2020)
Objective: to determine morphological and functional characteristics of different states of fitness in adolescence rowers. Materials and methods: 21 men athletes aged from 14 to 16 years of school of the Olympic reserve of the city of Rostov-on-Don (RWAR) involved in rowing were examined. We used the Dorokhov R.N. technique of selection and early orientation in sports to determine the anthropometric characteristics. Following functional indicators were defined: power index of both hands, the absolute physical efficiency (APE) with the help of РWС170 test, type of vegetative regulation with the help of method of heart rate variability assessment. Results: adolescence rowers had macrosomy and micromembrane somatotype. When the condition of exercise was insufficient, the following parameters were revealed: micromesocorpulent and mesomuscular somatotype, low power index of the brush, a low value of APE, expressed vagotonic type of autonomic regulation. If the condition of exercise was satisfactory, micromesocorpulent and micromesomuscular somatotype, the average power index of the brush below the average value of APE, mild vagotonic type of autonomic regulation were registered. The highest condition of exercise was associated with microcorpulent and mesomuscular somatotype, the average power index of the brush, the average value of APE normotonic type of vegetative regulation. Conclusions: certain morpho-functional parameters as: somatotype, level of power and absolute index of physical work efficiency and autonomic regulation defined an inadequate, satisfactory or a higher state of fitness.